The psa locus is responsible for thermoinducible binding of Yersinia pseudotuberculosis to cultured cells. - Yang, Y (1996)
Yersinia pseudotuberculosis inv mutant strains cured of the virulence plasmid exhibit thermoinducible adhesion to cultured mammalian cells. To identify the genes responsible for this phenotype, Y. pseudotuberculosis homologs of the Y. enterocolitica ail and the Y. pestis psa loci were identified. Mutations in the Y. pseudotuberculosis ail and psa loci were constructed and tested for thermoinducible binding. Results of cellular binding assays indicated that only mutations in psa, not in ail, resulted in defects for thermoinducible binding, with inv yadA psa strains showing no detectable cell adhesion. In addition, an inv psa strain was defective for hemagglutination of sheep erythrocytes, in contrast to an inv psa+ strain which was fully competent for hemagglutination. The introduction of a plasmid containing a 6.7-kb KpnI-ClaI fragment of Y. pseudotuberculosis encompassing the psa locus was sufficient to complement both the cell adhesion and hemagglutination defects of the psa mutant. Results from subcloning and transposon mutagenesis indicated that the complete 6.7-kb region was required for thermoinducible binding and hemagglutination.